Detecting neurodevelopmental problems in children aged 1-5 years using the simple parent-reported screening tool in combination with primitive reflex assessment - Nicholas Calvin; Yetty Ramli (Indonesian Pediatric Society, 2020)
Background The Kuesioner Pra Skrining Perkembangan/DPsQ (Developmental Pre-screening Questionnaire/DPsQ) is a series of questions and instructions used as a developmental screening tool for children aged 3 months to 6 years. However, the DPsQ cannot fully detect the soft signs of future neurological disorders. However, the retained primitive reflex assessment as an adjunct to the DPsQ may be useful for such detection. Objective To determine whether assessing for retained primitive reflexes can add to the usefulness of DPsQ as a neurodevelopmental screen in children aged 1 to 5 years. Methods This cross-sectional study included children aged 1-5 years. Developmental screening was done using the DPsQ and retained primitive reflex assessment was performed using the Institute for Neuro-Physiological Psychology (INPP) screening and scoring guideline. Results Of 46 subjects, 56.8% of children with normal DPsQ scores had not retained primitive reflexes, while 88.9% of children with suspect DPsQ score had retained primitive reflexes. Hence, children with suspect DPsQ score had a 10.5 times higher chance of retaining primitive reflexes (OR 10.50; 95%CI 1.19 to 92.73; P=0.034). Furthermore, 66.7-77.8% of children with suspect DPsQ score had retained the Moro reflex, asymmetrical tonic neck reflex (ATNR), and symmetrical tonic neck reflex (STNR). Neither gender nor age were significantly associated with either suspect DPsQ score or the presence of retained primitive reflexes. Conclusion The DPsQ results correlate to integration of primitive reflexes, with 10.50 greater odds of children with ‘suspect’ DPsQ scores to have retained primitive reflexes. As such, retained primitive reflexes is not useful as a primary screen for future neurological problems. However, a high percentage of children (43.2%) with normal DPsQ scores also have retained primitive reflexes.